1977
DOI: 10.2527/jas1977.4561382x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Profiles of Serum LH, FSH and Testosterone, and in Mating Performance and Ejaculate Volume in the Ram during the Ovine Breeding Season3

Abstract: Changes in profiles of serum luteinizing hormone (LH), follicle stimulating hormone (FSH) and testosterone and in mating performance and ejaculate volume have been determined in Finnish Landrace (Finn)and Managra Synthetic (Line-M) rams during the ovine breeding season. In early August, mid-September, early November and mid-December four rams of each breed were bled by venipuncture from the jugular vein at 20-min intervals for two 8-hr periods. Rams were bled while in the absence (control period) and presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 30 publications
5
25
1
Order By: Relevance
“…Since then, ER has also been described in the sheep adrenal gland (Van Lier et al, 2003b), supporting a possible role for oestrogens as modulators of cortisol secretion. Although in our experiment TC did not modify the cortisol response to ACTH in the rams, it cannot be ruled out that this might be due to the type of steroid replacement leading to sustained testosterone levels and not discrete pulses (Sanford et al, 1977). However, Broadbear et al (2005) did not detect differences in cortisol response after HPA stimulation of castrated rams with or without testosterone implant replacement (mean testosterone concentrations 6.11 nmol/l; lower than in the present study).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Since then, ER has also been described in the sheep adrenal gland (Van Lier et al, 2003b), supporting a possible role for oestrogens as modulators of cortisol secretion. Although in our experiment TC did not modify the cortisol response to ACTH in the rams, it cannot be ruled out that this might be due to the type of steroid replacement leading to sustained testosterone levels and not discrete pulses (Sanford et al, 1977). However, Broadbear et al (2005) did not detect differences in cortisol response after HPA stimulation of castrated rams with or without testosterone implant replacement (mean testosterone concentrations 6.11 nmol/l; lower than in the present study).…”
Section: Discussioncontrasting
confidence: 91%
“…The levels of 17β-oestradiol in the animals of experiment 1 were pharmacological and the dose of EB was therefore reduced in experiment 2, resulting in lower, yet still pharmacological levels of 17β-oestradiol in those animals. Testosterone levels of the animals in both experiments were within the physiological range, although by intramuscular administration the active compound is usually released into the bloodstream at a relatively steady rate and not in discrete pulses, as occurs in intact rams (Sanford et al, 1977).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, testosterone application seemed to stimulate accessory glands so that volume of ejaculated increased six-fold in T bucks compared to control bucks. Other researchers (Sanford et al 1977;Kishk 2008) also have observed an increased volume of ejaculates in rams with maximal levels of serum testosterone.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, feeding and environmental temperature (according to latitude) may modulate photoperiod effects [10,[19][20][21]. Finally, seasonal effects have been shown to differ among breeds [7,17,24,27]. Testosterone was measured by RIA using an anti-T-3-O-carboxymethyloxime-bovine serum albumin antiserum with a previous ether extraction of experimental sera, as described previously [29].…”
mentioning
confidence: 99%